Konseling Gizi Tentang Kejadian Stunting Di Desa Bajo Indah Kecamatan Soropia Kabupaten Konawe - Koro, Suriana; petrus, petrus; fatmawati, fatmawati; ahmad, ahmad (Poltekkes Kemenkes Kendari, 2023)
The stunting problem has quite serious impacts; among other things, the short term is related to morbidity and mortality in infants/toddlers, the medium term is related to low intelligence and cognitive abilities, and the long term is related to the quality of human resources and the problem of degenerative diseases in adulthood. The aim of this community service is for the community to recognize, understand and recognize the benefits and early detection of stunting events starting from the first 1000 days of life, the impact of stunting events. and to increase body endurance. The method used is nutritional counseling by providing education and counseling as well as discussions. Nutrition counseling can increase the knowledge of mothers in Bajo Indah village and understand the importance of eating a variety of foods that are nutritious, balanced, safe and healthy.